The Effectiveness of Assertiveness Training to Increase Self-Confidence in Early Adult Women Experiencing Body Dissatisfaction - Siti Aisyah Nuralifah Marimin; Faradillah Firdaus; Tri Sulastri (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Self-confidence experienced by early adult women adversely affects their individual interpersonal relationships. This study aims to determine the effect of assertive training in increasing self-confidence in early adult women who experience body dissatisfaction. This study used a quasi-experimental design with a one-group pretest-posttest approach involving 8 women aged 18-22 years with the criteria of experiencing high levels of body dissatisfaction and low levels of self-confidence. Data were collected using body dissatisfaction and self-confidence measurement scales, as well as observation to record relevant information or behaviors of participants, and an intervention in the form of assertive training conducted over six sessions within in 2-day period. The results of the analysis using the Wilcoxon Test showed a significance value of 0.012 (p < 0.05), indicating an statistically significant increase in self-confidence. The evaluation of knowledge showed a significance value of 0.014 (p < 0.05), indicating an increase in understanding among participants. Based on the study's results, it can be concluded that assertive training has a significant impact on individual self-confidence. Keywords: body dissatisfaction, self-confidence, assertive behavior, early adult women